Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1189/jlb.1105623
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCR7 monoclonal antibodies as a novel tool for the treatment of chronic lymphocyte leukemia

Abstract: To date, chronic lymphocytic leukemia (CLL) remains incurable with current treatments, which include the monoclonal antibodies (mAbs) rituximab and alemtuzumab. The efficacy of rituximab is modest when used as single agent, and alemtuzumab induces severe immunosuppression. To develop more potent and specific therapies, we propose the CC chemokine receptor 7 (CCR7) as an attractive target molecule to treat CLL, as it not only fulfills the requirements of a high-surface expression and a good level of tissue spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 59 publications
3
39
1
Order By: Relevance
“…CCR7 targeting might work not only by interfering with tumor cell homing, and thereby metastases, but also by reducing the growth of these tumors. Alfonso-Perez and colleagues (49) have demonstrated a largely specific lysis of CCR7-positive lymphoma cells in vitro by using Ab-mediated complement cytotoxicity. Although we used another approach, this work shows that the high expression of CCR7 in tumor cells makes them an easy target for CCR7-directed therapy.…”
Section: Does the Demonstrated Inhibitory Effect Apply To Physiologicmentioning
confidence: 99%
“…CCR7 targeting might work not only by interfering with tumor cell homing, and thereby metastases, but also by reducing the growth of these tumors. Alfonso-Perez and colleagues (49) have demonstrated a largely specific lysis of CCR7-positive lymphoma cells in vitro by using Ab-mediated complement cytotoxicity. Although we used another approach, this work shows that the high expression of CCR7 in tumor cells makes them an easy target for CCR7-directed therapy.…”
Section: Does the Demonstrated Inhibitory Effect Apply To Physiologicmentioning
confidence: 99%
“…By inhibition of these pathways, B-CLL cells were no longer protected from undergoing apoptosis. Due to the high surface expression and tissue specificity of CCR7 in B-CLL cells, Alfonso-Perez et al [13] proposed a murine anti-CCR7 monoclonal antibody as a new therapeutical agent. They report on a potent, complement-dependent cytotoxicity against B-CLL cells whilst sparing normal T lymphocytes from the same patient.…”
Section: Ccl19 Ccl21 and Their Common Receptor Ccr7mentioning
confidence: 99%
“…For this reason, therapeutic targeting of chemokine activity has become the focus of extensive pharmaceutical research [10][11][12]. B-CLL cells possess a characteristic chemokine receptor profile; hence, receptor inhibition could function as a promising tool for treatment [13]. In addition, since the expression of some chemokines and chemokine receptors correlates with important and well-established predictive clinical parameters, they might be implemented as new diagnostic markers [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported a strong correlation between the expression of CCR7 by solid tumor cells and the presence of LN metastases (2). These findings prompted us to investigate a possible role of CCR7 as therapeutic target for CLL and demonstrated that anti-CCR7 monoclonal antibodies (mAbs) efficiently eliminated CLL cells in vitro (18).…”
Section: Introductionmentioning
confidence: 99%